Investigating the thermophysical properties and ignition behaviour in CI engines of cost-effective gasoline-palm biodiesel-diesel blends - Zandie, Mohammad (2024)
In this thesis a compact combined reaction mechanism for diesel-biodiesel-gasoline mixtures (CDBG) is developed. The detailed mechanisms were separately reduced prior to combining by means of directed relation graph (DRG), directed relation graphs with error propagation (DRGEP), and full species sensitivity analysis (FSSA). The reduced mechanisms were then combined and validated under closed homogenous reactor conditions at T=600-1700 K, P=1-50 atm, and equivalence ratios (Φ) of 0.25-1.5 (156 setups in total).